2022
DOI: 10.3390/molecules27248855
|View full text |Cite
|
Sign up to set email alerts
|

Silymarin Protects against Acute Liver Injury Induced by Acetaminophen by Downregulating the Expression and Activity of the CYP2E1 Enzyme

Abstract: Previous studies have shown that silymarin protects against various types of drug-induced liver injury, but whether the protective mechanism of silymarin against acetaminophen-induced liver injury is related to the CYP2E1 enzyme remains unclear. In this study, we investigated the effect of silymarin on the activity and expression of CYP2E1 in vitro and in vivo. The results of in vitro studies showed that silymarin not only inhibited the activity of CYP2E1 in human and rat liver microsomes but also reduced the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Silymarin has been reported to act as an antioxidant by reducing free radical production and lipid peroxidation, function as a toxin blocker by inhibiting the binding of toxins to the hepatocyte cell membrane receptors ( Abenavoli et al, 2010 ), and reduce the superoxide and peroxynitrite content by its scavenger activity ( Papackova et al, 2018 ). Recent research has shown that silymarin reduces acute toxic liver injury caused by APAP by increasing hepatocyte proliferation, decreasing CYP2E1 activity and expression, and decreasing the production of toxic metabolites ( Elsayed Elgarawany et al, 2020 ; Ihedioha et al, 2020 ; Yang et al, 2022b ). Silibinin is the major active component of silymarin.…”
Section: Effects and Mechanism Of Natural Products In Acetaminophen-i...mentioning
confidence: 99%
“…Silymarin has been reported to act as an antioxidant by reducing free radical production and lipid peroxidation, function as a toxin blocker by inhibiting the binding of toxins to the hepatocyte cell membrane receptors ( Abenavoli et al, 2010 ), and reduce the superoxide and peroxynitrite content by its scavenger activity ( Papackova et al, 2018 ). Recent research has shown that silymarin reduces acute toxic liver injury caused by APAP by increasing hepatocyte proliferation, decreasing CYP2E1 activity and expression, and decreasing the production of toxic metabolites ( Elsayed Elgarawany et al, 2020 ; Ihedioha et al, 2020 ; Yang et al, 2022b ). Silibinin is the major active component of silymarin.…”
Section: Effects and Mechanism Of Natural Products In Acetaminophen-i...mentioning
confidence: 99%
“…Regarding CYP2E1, a member of the cytochrome P450 superfamily that participates effectively in the conversion of CCl 4 into free radicals, silymarin demonstrates a noteworthy decrease in CYP2E1 levels [ 69 ]. This reduction in CYP2E1 levels led to a decrease in free radical production and, subsequently, mitigated the induction of liver injury [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many other natural compounds such as silymarin, resveratrol, curcumin, and berberine have effectively prevented the progression of MASLD and MASH [ 363 , 364 ]. Some of these naturally occurring compounds function as antioxidants and inhibitors of CYP2E1 [ 365 367 ] to prevent ALD, MASLD, and DILI. In addition, many naturally occurring antioxidants, including resveratrol, quercetin, and curcumin, are known to activate sirtuins, Nrf2, and PGC1α to improve liver disease outcomes [ 85 , 138 , 139 , 363 , 364 , 368 ].…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%